Pendekatan Komunikatif David Nunan (Studi Kasus dalam Pembelajaran Bahasa Arab di Markas Bahasa Arab Pondok Pesantren Banyuanyar Pamekasan) - Mabrurrosi Mabrurrosi; Lutfi Aziz; Ruji Ruji (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2023)
The Communicative Approach, also known as communicative language teaching (CLT), emphasizes interaction and problem solving as both a means and an end goal of learning a particular language. This approach emphasizes role-playing activities such as language learning activities in pairs and language learning in certain groups. This results in the transfer of the role and focus of learning from teacer oriented to student oriented, namely students as the main focus and active actors of learning. The implementation of Arabic learning at the Arabic language headquarters of the Banyuanyar Islamic boarding school has largely been in accordance with the communitive approach initiated by David Nunan